The Use of Story-Telling Techniques for Improving Students' Speaking Ability - Hermansyah, Hendro; Hastomo, Tommy; Abdullah, Abdullah (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2019)
This study aims to improve speaking skills through storytelling techniques for class VIII G students of SMP Negeri 21 Bandar Lampung. This research method is Classroom Action Research (CAR). Data collection techniques in this study were interviews, observations, questionnaires, and documentation. The data analysis technique was based on observation and speaking skill tests through storytelling techniques. From the analysis of observation data, speaking skills through storytelling techniques for class VIII G SMP Negeri 21 Bandar Lampung in the pre-action stage obtained an average score of 11.53, in the post-action cycle I increased to 14.13, and in the post-action cycle II also increased to 16.06. Based on the results of the study, it can be concluded that storytelling techniques can improve speaking skills in class VIII students of SMP Negeri 21 Bandar Lampung.